Income Contingency and the Repayment of Student Loans - Rowley, J. C.R. (Journal of Income Distribution®, 1994)
The current systems of financial support to postsecondary students in Canada and elsewhere are clearly inadequate. Their evident deficiencies have revived interest in the possibility of income-contingent loans and in the use of the tax system to deal with repayments. Some simulative experiments are used here to explore the feasibility of income contingency and to explore the sensitivity of financial flows to various assumptions about interest rates, income growth, age-earning profiles, default, and take-up rates for loans. Evidence from these experiments points to some salient features in the design of new schemes or the support of postsecondary students, and it also permits the identification of relevant issues which might significantly affect the practical implementation of any scheme involving income contingence as a basis for repayments.